Implementación de una plataforma informática colaborativa para la publicación digital de artículos científicos en la Revista DATEH de la Universidad Técnica de Cotopaxi - Extensión La Maná. - Calo Pallo, Ruth Noemi (2020)
The present project consists of implementing a computer platform that will support the Multidisciplinary Electronic Journal DATEH (Desarrollo Empresarial, Agropecuario, Tecnológico y Humanista) for the national and international diffusion of scientific articles resulting from research, not only from the Technical University of Cotopaxi, but also from various educational and/or research centers in different parts of the world. The initial part of the project guarantees the necessary infrastructure to support the electronic journal. Among the most important elements of this stage are the server and the study, installation and configuration of the operating systems and web services software available today. The second stage of the project is the implementation of the computer platform that manages the journal's own information such as authors, articles, reviewers, among others. The corresponding software engineering tests are carried out to guarantee the quality of the system and it is made public within the institution's Intranet. The final stage of the project consists of the incorporation of the characteristics and modules that conform the standard in its version 2.0 of the nonprofit academic information system LATINDEX.